2007
DOI: 10.1007/bf03026790
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine for preventing acute kidney injury in cardiac surgery patients with pre-existing moderate renal insufficiency

Abstract: Purpose: N-acetylcysteine may prevent acute kidney injury after cardiac surgery. To determine if N-acetylcysteine warrants definitive evaluation in a large multicentre trial, we evaluated its effects on a surrogate outcome, estimated glomerular filtration rate (eGFR), in a randomized trial. Methods:One-hundred-seventy-seven cardiac surgery patients with moderate pre-existing renal insufficiency (eGFR ≤ 60 mL·min -1 ) were recruited in a blinded (patients, clinicians, datacollectors) placebo-controlled randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 48 publications
1
66
0
1
Order By: Relevance
“…In addition, because patients with kidney dysfunction are at increased risk for adverse cardiovascular outcomes after major surgery they may benefit from aggressive treatment of atherosclerotic risk factors and potentially the targeted use of therapeutic interventions such as statin therapy. 78 Similarly, interventions such as N-acetyl cysteine 79 might potentially be used to prevent renal injury. In conclusion, we have found that kidney function, defined using eGFR, predicts cardiovascular events and AKI after, predominantly cardiac and vascular, surgery and, in particular, exhibits a powerful inverse nonlinear relationship with all-cause mortality in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because patients with kidney dysfunction are at increased risk for adverse cardiovascular outcomes after major surgery they may benefit from aggressive treatment of atherosclerotic risk factors and potentially the targeted use of therapeutic interventions such as statin therapy. 78 Similarly, interventions such as N-acetyl cysteine 79 might potentially be used to prevent renal injury. In conclusion, we have found that kidney function, defined using eGFR, predicts cardiovascular events and AKI after, predominantly cardiac and vascular, surgery and, in particular, exhibits a powerful inverse nonlinear relationship with all-cause mortality in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wijeysundera et al [11] found that there was preservation of postoperative eGFR in patients with preexisting moderate renal dysfunction undergoing cardiac surgery and a significant reduction in mortality with NAC. In our study, we observed increased creatinine clearance and augmented eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…1). A total of 70 studies (5,554 patients) met eligibility criteria [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86] (table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Predefined criteria for acute renal replacement therapy initiation were provided in 7 of these studies and were not uniform across studies [25,27,40,55,56,77,81]. In 1 case, initiation was determined by blinded nephrologists without specific parameters described [81].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation